Does internet access increase the perception of corruption? - Yi, Chengzhi (Crime, law and social change, 2022)
This article used the 2018 China Family Panel Studies (CFPS2018) data to systematically examine the impact of Internet access on corruption perceptions and its mechanisms. After controlling for a series of variables such as demographic characteristics and cultural and psychological factors, this study found that there is a significant correlation between Internet access and individuals’ perception of corruption, which could be attributed to the characteristics of the Internet and the individuals’ "negativity bias effect". In addition, a mechanism analysis found that both political trust and relative deprivation played an incomplete intermediary role between Internet use and the perception of corruption and between Internet use time and the perception of corruption, which is consistent with the explanations of a "negativity bias effect", a "halo effect" and "self-serving attribution bias". The moderating role of authoritative value orientation between Internet access and the perception of corruption was not obvious.